Genetic population structure of Japanese freshwater crab, Geothelphusa dehaani species complex using genome wide SNPs - Taiga Kunishima; Kento Takata; Kanto Nishikawa; Kodai Gibu; Miyuki Nishijima; Akira Iguchi (Scientific Reports)
Abstract The Japanese freshwater crab Geothelphusa dehaani species complex is distributed widely across the Japanese Archipelago. Despite its suggested high genetic and morphological diversity, key aspects such as nuclear DNA (nuDNA) population structure and relationship between body color patterns and genetic populations remain unclear. To address these gaps, this study analyzed genome-wide single nucleotide polymorphisms (SNPs) in nuDNA and mitochondrial DNA (mtDNA) cytochrome oxidase subunit 1 (COI) markers in samples from Hokkaido to the Tokara Islands, Japan. ADMIXTURE analysis identified five distinct populations with significant geographic boundaries. These populations exhibited unique geographical patterns, spanning across islands and enclave distribution, indicating that G. dehaani populations have been shaped by complex factors, including sea level changes and volcanic activity. Regional body color variations partially aligned with SNP clades. Further, combining body color with collection locality data could help identify the specimen populations. Contrasting patterns between mtDNA and nuDNA suggest historical gene flow and introgression, emphasizing the need for caution when interpreting earlier phylogenetic studies based on combined mtDNA and nuDNA sequences. Our findings provide a foundational baseline for future research into the taxonomy, phylogeny, and population dynamics of the G. dehaani species complex, advancing our understanding of its evolutionary history.